Degradation Kinetics and Mechanical Studies of Intumescent Coated Cotton Fabric - Kumar, Satish; Lal, Sohan; Arora, Sanjiv (Journal of Research Updates in Polymer Science, 2015)
In the present study, cotton fabric were prepared via coating with intumescent formulations of ammonium polyphosphate (APP), guanidine nitrate, penta erythritol (PER) and metal salts at different loading levels via ‘Pad-dry cure’ method. Thermal degradation behavior of prepared cotton derivatives was investigated by thermogravimetry (TG) and differential thermal analysis (DTA) from ambient temperature to 700 oC. Dynamic TG analysis was used to study the thermal degradation behavior of samples at four different heating rates of 2, 5, 10 and 20 oC min-1 in air atmosphere. The treated cotton fabric decomposes at lower temperatures and produces higher amount of char yields. The degradation activation energy was calculated using Friedman, modified Coats-Redfern and Ozawa-Flynn-Wall (O-F-W) iso-conversional model free methods. Tensile properties of coated fabric were found to be reduced with increase in loading of intumescent formulation but there was an abrupt increase in sample coated with intumescent and silica. With the insertion of iron (Fe) metal ion along with intumescent reduces the fabric strength due to formation of metal complexes with cotton cellulose which decreases the crosslinking. The maximum flame ratardancy of CF 12APP-Si among all cotton derivatives is suggested as the flame retardancy directly proportional to char yield (22 % at 650 oC) that is highest and inversely proportional to MMLR value (8.3 % min-1), that is least among all samples. Based on thermal and kinetic studies, the optimum concentration of flame retardant is worked out.